Antioxidant and chemopreventive effects of Asperugo procumbens in a rat model of hepatocellular carcinoma - Arabsalmani, Mahdieh; Hosni, Mahsa; H Shirazi, Farshad; Andalib, Sina; Gholami, Saman; Hosseini, Seyed Hojjat; Kamalinejad, Mohammad; Noubarani, Maryam; Shamseini, Mohadeseh; Eskandari, Mohammad Reza (International Pharmacy Acta, 2020)
Introduction: Hepatocellular carcinoma (HCC) cancer is the fifth most common malignancy, with 0.25–1 million new cases diagnosed annually worldwide. The objective of the present study was to evaluate the antioxidant and chemopreventive effects of aqueous extract of Asperugo procumbens L. (AAP) against diethylnitrosamine (DEN)-induced hepatocellular carcinoma (HCC) in rats. Methods and Results: The model of hepatocellular carcinoma was induced by a single intraperitoneal injection of DEN (200 mg/kg) as an initiator that after two weeks followed by daily oral administration of 2-acetylaminofluorene (30 mg/kg) as a promoter for two weeks. AAP-treated rats were pretreated with the extract intragastrically at three different doses two weeks prior to DEN injection. At the end of the experiment, the marked reduction of serum biomarkers of liver damage and cancer, including alfa-fetoprotein (AFP), gamma glutamyl transpeptidase (GGT), alanine transaminase (ALT), and aspartate transaminase (AST) were observed in AAP complemented rats as compared to DEN-treated animals. Besides, the extract exhibited in vivo antioxidant activity that evident by increasing GSH concentration along with lipid peroxidation prevention in the liver tissues of HCC animals. In addition, A. procumbens showed in vitro free radical scavenging activity that determined by 1, 1-Diphenyl-2-picryl hydroxyl (DPPH) antioxidant assay. The relative weight of liver was also reduced in AAP-treaded rats as a prognostic marker in HCC. Conclusions: Our results obviously confirmed that A. procumbens possesses a chemopreventive effect against primary liver cancer induced by DEN in rats as well as in vitro and in vivo antioxidant activities.